Breeding and nursery culture of sebarau, Hampala macrolepidota (Van Hasselt and Kuhl, 1823) - Zaharin, Intan Khairulnisa (2015)
Hampala macrolepidota or locally known as sebarau, is a native carp species of Malaysia, yet not a popular fish for aquaculture. This may be due to the lack of seed supply and proper nursery culture technique. This study was aimed to breed H. macrolepidota using Ovaprim, to observe its embryonic stages and to determine the effects of different salinity, pH, dietary protein and stocking density on the growth and survival of its fry.